The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3855/jidc.1857
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of conventional molecular diagnosis of Mycobacterium tuberculosis in clinical specimens from Morocco

Abstract: Introduction: Tuberculosis is a major public health threat, annually affecting new individuals worldwide, especially those in developing countries. Rapid detection of the agent and effective treatment are two important factors in controlling this disease. Methodology: The present study aimed to evaluate polymerase chain reaction (PCR) as a rapid and direct molecular method for the diagnosis of Mycobacterium tuberculosis (MTB) in 70 clinical specimens (62 sputum samples, six cerebrospinal fluids, and two biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, PCR targeting 16S rDNA gene can not differentiate between the closely related species of mycobacteria 10. The hsp65 was also reported to be used as a target for PCR testing to detect MTB DNA in clinical cases, but the necessity of sequencing is still mandatory for the differentiation between the complex MTB and other non tuberculosis mycobacteria 11,29…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PCR targeting 16S rDNA gene can not differentiate between the closely related species of mycobacteria 10. The hsp65 was also reported to be used as a target for PCR testing to detect MTB DNA in clinical cases, but the necessity of sequencing is still mandatory for the differentiation between the complex MTB and other non tuberculosis mycobacteria 11,29…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity, specificity, positive predictive value, negative predictive value, positive rate, and diagnostic efficiency of our modified acid-fast staining method were evaluated by using the PCR method as the comparison's gold standard (Vishnevskaia et al, 2001;Alli et al, 2011;Chen et al, 2012;Zakham et al, 2012). Briefly, fifty sputum samples from patients with confirmed tuberculosis were analyzed by comparing results from our modified acid-fast staining method and the PCR method .…”
Section: Evaluation Of Our Modified Acid-fast Staining Methodsmentioning
confidence: 99%
“…The presence of PCR inhibitors has been reported in sputum, pus samples, and tissue biopsies. [ 23 ] Shrivastav et al . in 2014[ 24 ] found that PCR-negative samples in endometrial tissue were positive by culture methods and concluded that DNA-PCR done alone is not reliable for TB diagnosis, it should be combined with culture.…”
Section: Tests For Genital Tuberculosismentioning
confidence: 99%